Rectal mucocele in the anterior wall of the rectum. (18th May 2018) - Ishii, Daisuke; Aoki, Takanori; Inaba, Satoshi; Yabuki, Hidehiko
Abstract : An 84-year-old man presented in 2009 with a sensation of discomfort in his anus, combined with difficulty in urination. He had previously undergone a haemorrhoidectomy in 1964. After examination, he was diagnosed with a rectal mucosal cyst and followed up for observation. In 2015, he presented to our hospital complaining that the cyst was prolapsing from his anus. CT revealed a 48×41 mm cystic mass in the anterior wall of the rectum. Tumour extirpation, via a transanal route, was performed. The postoperative pathological diagnosis confirmed a rectal mucocele. Rectal mucoceles are extremely rare, with no prior report of a mucocele in the anterior wall of the rectum. In this case, we believe the mucocele developed from an invagination of the mucous membrane or obstruction of the anal gland during suturing during the previous haemorrhoid surgery.